Porous foamy carbon material and preparation method thereof
By using alloy powder to react with liquid carbon source in super-rigid carbon dioxide media, the problem of insufficient structural stability of carbon materials is solved, and the preparation of porous foam carbon materials with high strength and high graphitization is achieved, satisfying multiple fields Application requirements.
Patent Information
- Application Number
- CN202411631284.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-14
AI Technical Summary
The structural stability of existing carbon materials is insufficient, making it difficult to meet the needs of complex applications, and the introduction of two metals may lead to uneven morphology.
In a supercritical carbon dioxide medium environment, alloy powder is used to react with liquid carbon source, and the structural changes of the liquid carbon source are promoted through the synergistic catalysis of the alloy powder, forming a porous foam carbon material with a high degree of graphitization.
The strength and structural stability of carbon materials are improved, and the porous foam carbon structure with excellent structural stability is formed to meet the application needs of multiple fields.
Smart Images

Figure CN119430143A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon materials, and in particular to a porous foam carbon material and a preparation method thereof. Background Art
[0002] Carbon materials are extremely abundant in nature, have stable properties, and are highly friendly to the environment. Therefore, carbon materials are widely used in many fields, such as being used as battery materials to provide reliable energy storage and release functions for various electronic devices; acting as adsorption materials to efficiently remove harmful substances in the environment; and acting as catalytic materials to accelerate chemical reactions.
[0003] Metals have a significant impact on the structure and morphology of carbon materials. For example, metals such as iron, cobalt, and nickel can act as catalysts to promote the formation of graphene under specific conditions; metals such as copper and zinc can act as activators to enable carbon materials to form porous forms with specific structures.
[0004] However, a single metal cannot cause uniform changes in the structure of carbon materials, and has fewer active sites, requires higher temperatures, and takes longer to react, resulting in insufficient structural stability of the carbon materials and making it difficult to meet complex application requirements. The introduction of two metals may cause problems such as agglomeration and oxidation during the reaction, making the morphology of the formed carbon materials uneven. Summary of the invention
[0005] Based on this, it is necessary to provide a porous foam carbon material and a preparation method thereof to address the above problems; the preparation method described in the present invention can produce a porous foam carbon material with a special morphology and structure, and improve the strength and structural stability of the carbon material, which can meet the application needs in multiple fields.
[0006] The present invention provides a method for preparing a porous foam carbon material, comprising the following steps:
[0007] The alloy powder, liquid carbon source and dry ice are mixed and reacted in a supercritical carbon dioxide medium environment formed under sealed heating conditions to obtain a porous foam carbon material.
[0008] In one embodiment of the present invention, the mass ratio of the alloy powder to the liquid carbon source is 10:4-10:6.
[0009] In one embodiment of the present invention, the mass ratio of the liquid carbon source to the dry ice is 4:20-6:20.
[0010] In one embodiment of the present invention, the alloy powder is selected from at least one of copper-nickel alloy powder and iron-nickel alloy powder.
[0011] In one embodiment of the present invention, the liquid carbon source is selected from at least one of ethanol and toluene.
[0012] In one embodiment of the present invention, before sealing and heating, the alloy powder and the liquid carbon source are first mixed at room temperature and pressure, and then dry ice is added for sealing and heating.
[0013] In one embodiment of the present invention, the reaction temperature is 500°C-700°C, the heating rate is 4°C / min-6°C / min, and the reaction time is 4h-6h.
[0014] In one embodiment of the present invention, after the reaction is completed, a wet treatment is further included, and the temperature of the wet treatment is 70° C.-80° C., and the time is 12h-18h.
[0015] In one embodiment of the present invention, the mixture after wet treatment is subjected to solid-liquid separation, and the separated solid is dried at 70° C.-80° C. for 12 h-18 h.
[0016] The present invention also provides a porous foam carbon material prepared by the method for preparing the porous foam carbon material as described above.
[0017] The preparation method of the present invention introduces alloy powder to assist the liquid carbon source in reacting under supercritical carbon dioxide medium conditions, and has the following three advantages: first, supercritical carbon dioxide is used as a reaction medium, which can provide a more uniform reaction environment for the alloy powder to change the morphology and structure of the liquid carbon source, so that the alloy powder can play a more effective role, promote the change of the structure of the liquid carbon source, increase the degree of graphitization of the carbon material, and improve its mechanical properties. At the same time, supercritical carbon dioxide can also evenly penetrate into the liquid carbon source, which is conducive to promoting the formation of pores inside, thereby obtaining a porous foam carbon structure with excellent structural stability; second, the liquid carbon source can make the reaction more uniform, which is more conducive to promoting carbon formation. The invention discloses a novel nanostructured carbon foam having a plurality of carbon nanotubes and a plurality of graphene layers, wherein the carbon nanotubes are composited with graphene and cross-linked with each other to improve the mechanical strength and flexibility of the carbon material, thereby forming a porous foam carbon material with high strength and high degree of graphitization.
[0018] Therefore, the porous foam carbon material prepared by the preparation method provided by the present invention not only has rich pores and pore structure distribution effects, which is beneficial to improving the adsorption performance and energy storage capacity of the carbon material, and can provide more active sites for chemical reactions, but also has high strength and excellent structural stability, and can meet the application requirements in multiple fields such as adsorption, catalysis and secondary batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0020] Figure 1 This is an X-ray diffraction pattern of the porous foam carbon material prepared in Example 2 of the present invention;
[0021] Figure 2 This is a Raman spectrum of the porous foam carbon material prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0022] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.
[0024] The present invention provides a method for preparing a porous foam carbon material, comprising the following steps:
[0025] The alloy powder, liquid carbon source and dry ice are mixed and reacted in a supercritical carbon dioxide medium environment formed under sealed heating conditions to obtain a porous foam carbon material.
[0026] Supercritical carbon dioxide is a gas in a special state where the temperature and pressure are higher than its critical point. The preparation method described in the present invention uses supercritical carbon dioxide as a reaction medium. By improving the thermal conductivity of the reaction space, it can provide a more uniform reaction environment for the alloy powder to change the morphology and structure of the liquid carbon source, so that the alloy powder can play a more effective role, which can not only accelerate the chemical reaction rate and promote the change of the structure of the liquid carbon source, but also help to improve the graphitization degree of the carbon material, based on the high-pressure environment provided by supercritical carbon dioxide, reduce the atomic distance, and then improve the density of the carbon material and improve its mechanical properties. At the same time, supercritical carbon dioxide can also evenly penetrate into the liquid carbon source, which is conducive to promoting the formation of microporous structure, mesoporous structure and macroporous structure in the carbon material, and then obtain a porous foam carbon structure with excellent structural stability.
[0027] Compared with traditional solid carbon sources, the liquid carbon source used in the present invention can make the reaction more uniform, is more conducive to promoting carbon structure transformation, and improves the uniformity of pore structure distribution in carbon materials. In addition, the liquid carbon source is highly accessible and has excellent safety, which is more conducive to industrial production and has broad application prospects.
[0028] The present invention also uses alloy powder to produce a synergistic catalytic effect on the liquid carbon source. On the one hand, the alloy powder has a larger specific surface area and can provide more active sites, thereby making the growth process of the carbon structure more efficient. On the other hand, since the alloy powder has a unique electronic structure and chemical properties, it can form a specific interaction with the liquid carbon source, guiding the liquid carbon source to grow and assemble in an orderly manner in a supercritical carbon dioxide medium environment, promoting the liquid carbon source to transform into carbon nanotubes and graphene, and then forming a porous foam carbon material with high strength and high degree of graphitization.
[0029] Therefore, the present invention prepares a porous foam carbon material with good mechanical properties, high strength and bulkiness by cleverly combining alloy powder, liquid carbon source and supercritical carbon dioxide medium conditions.
[0030] By regulating the amount of alloy powder and liquid carbon source involved in the reaction, it is beneficial to further optimize the structure and mechanical properties of the porous foam carbon material.
[0031] Preferably, the mass ratio of the alloy powder to the liquid carbon source is 10:4-10:6, including but not limited to any value among 10:4, 10:5, 10:6 or a range between any two of them.
[0032] By regulating the amount of dry ice in the reaction system, it is beneficial to further improve the reaction uniformity and reaction efficiency, thereby optimizing the structure and mechanical properties of the porous foam carbon material.
[0033] Preferably, the mass ratio of the liquid carbon source to the dry ice is 5:15-5:25, including but not limited to any point value of 5:15, 5:18, 5:20, 5:25 or a range value between any two of them, more preferably 4:20-6:20.
[0034] In one embodiment of the present invention, the alloy powder includes but is not limited to binary alloy powder composed of two metal elements, multi-element alloy powder composed of three or more metal elements, such as ternary alloy powder, quaternary alloy powder, etc.
[0035] Preferably, the alloy powder is selected from binary alloy powder.
[0036] Specifically, the alloy powder includes but is not limited to at least one of copper-nickel alloy powder and iron-nickel alloy powder.
[0037] Further preferably, the alloy powder is selected from nickel-copper alloy. On the one hand, nickel-copper alloy can promote the formation of graphene and improve the degree of graphitization of carbon materials; on the other hand, nickel-copper alloy can also form loose and porous carbon nanotubes, which effectively inhibit the deformation of carbon materials.
[0038] In one embodiment of the present invention, the liquid carbon source is preferably an organic liquid carbon source.
[0039] It is understandable that the liquid carbon source includes but is not limited to at least one of an alcohol organic liquid carbon source and toluene.
[0040] Specifically, the alcohol organic liquid carbon source includes but is not limited to at least one of ethanol and toluene.
[0041] In one embodiment of the present invention, the liquid carbon source is preferably ethanol, which is not only conducive to reducing costs, but also under the action of the alloy powder, carbonization can occur when the reaction temperature reaches above 300° C., thereby improving the reaction efficiency.
[0042] In one embodiment of the present invention, before sealing and heating, the alloy powder and the liquid carbon source are first mixed at room temperature and pressure, and then dry ice is added for sealing and heating, which is more conducive to the alloy powder fully acting on the liquid carbon source.
[0043] It can be understood that normal temperature includes 10°C-30°C, and normal pressure includes below 0.1MPa.
[0044] In one embodiment of the present invention, the reaction temperature is 500°C-700°C, including but not limited to any point value among 500°C, 550°C, 600°C, 650°C, 700°C or any range value between two of them; the heating rate is 3°C / min-7°C / min, including but not limited to any point value among 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min or any range value between two of them; the reaction time is 4h-6h, including but not limited to any point value among 4h, 5h, 6h or any range value between two of them.
[0045] It can be understood that the above reaction temperature is the working temperature of the reaction device; the reaction time is the time taken for the heat preservation reaction after reaching the reaction temperature at a certain heating rate.
[0046] In one embodiment of the present invention, a wet treatment is further included after the reaction is completed. The wet treatment can effectively remove impurities in the reaction product, which is beneficial to improving the purity and quality of the obtained porous foam carbon material.
[0047] Preferably, wet treatment is carried out under heating conditions, which is more conducive to fully removing impurities in the reaction product.
[0048] In one embodiment of the present invention, the temperature of the wet treatment is 70°C-80°C, including but not limited to 70°C, 75°C, 80°C, any point in between or any range between two of them; the time is 12h-18h, including but not limited to 12h, 14h, 16h, 18h, any point in between or any range between two of them.
[0049] It can be understood that the wet treatment includes acid solution wet treatment and alkaline solution wet treatment. The present invention preferably adopts acid solution wet treatment, wherein the acid solution includes but is not limited to at least one of hydrochloric acid and sulfuric acid, and the concentration of the solute in the acid solution is preferably 3mol / L-5mol / L.
[0050] In one embodiment of the present invention, the mixture after the wet treatment is subjected to solid-liquid separation, and the separated solid is dried at 70° C.-80° C. for 12 h-18 h.
[0051] It should be noted that the above-mentioned solid-liquid separation method includes but is not limited to centrifugal separation. The present invention preferably adopts centrifugal separation, wherein the rotation speed of the centrifugal separation is 8000r / min-12000r / min.
[0052] The present invention also provides a porous foam carbon material prepared by the method for preparing the porous foam carbon material as described above.
[0053] The porous foam carbon material described in the present invention not only has abundant pores and pore structure distribution effects, which is beneficial to improving the adsorption performance and energy storage capacity of the carbon material and can provide more active sites for chemical reactions, but also has high strength and excellent structural stability, and can meet the application requirements in multiple fields such as adsorption, catalysis and secondary batteries.
[0054] It is understandable that the present invention does not limit the shape of the porous foam carbon material. Generally speaking, the porous foam carbon material that has not been crushed is generally a block material. Those skilled in the art can crush the porous foam carbon block material to different degrees according to actual application requirements to obtain powders with different particle sizes.
[0055] The porous carbon foam material and its preparation method will be further described below by the following specific examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, the conventional conditions or the conditions recommended by the manufacturer are followed. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0056] Example 1
[0057] 10 g of copper-nickel alloy powder was added to a high-temperature reactor, and then 7 mL of ethanol was added and stirred evenly, and then 20 g of dry ice was added, and the temperature was increased to 500°C at a heating rate of 5°C / min, and kept warm for 5 hours. After the high-temperature reactor was completely cooled to room temperature, the reaction product was taken out, and the reaction product was soaked in 5 mol / L hydrochloric acid for pickling at 70°C for 12 hours, and then centrifuged at a speed of 10000 r / min to separate the solid and liquid, and the solid product after solid-liquid separation was dried in an oven at 70°C and ground with a mortar to obtain a porous foam carbon material.
[0058] Example 2
[0059] 10 g of copper-nickel alloy powder was added to a high-temperature reactor, and then 7 mL of ethanol was added and stirred evenly, and then 20 g of dry ice was added, and the temperature was increased to 600 ° C at a heating rate of 5 ° C / min, and kept warm for 5 hours. After the high-temperature reactor was completely cooled to room temperature, the reaction product was taken out, and the reaction product was soaked in 5 mol / L hydrochloric acid for pickling at 70 ° C for 12 hours, and then centrifuged at a speed of 10000 r / min to separate the solid and liquid, and the solid product after solid-liquid separation was dried in a 70 ° C oven and ground with a mortar to obtain a porous foam carbon material.
[0060] The porous carbon foam material prepared in this embodiment was subjected to X-ray diffraction analysis and Raman spectroscopy analysis. The results are as follows: Figure 1 and Figure 2As shown, according to Figure 1 and Figure 2 It can be seen that the carbon peak of XRD is relatively sharp, indicating that the obtained material has a high degree of crystallinity and strong stability. Combined with Raman spectroscopy, it can be seen that the degree of graphitization of the material is high.
[0061] Example 3
[0062] 10 g of copper-nickel alloy powder was added to a high-temperature reactor, and then 7 mL of ethanol was added and stirred evenly, and then 20 g of dry ice was added, and the temperature was increased to 700 ° C at a heating rate of 5 ° C / min, and kept warm for 5 hours. After the high-temperature reactor was completely cooled to room temperature, the reaction product was taken out, and the reaction product was soaked in 5 mol / L hydrochloric acid for pickling at 70 ° C for 12 hours, and then centrifuged at a speed of 10000 r / min to separate the solid and liquid, and the solid product after solid-liquid separation was dried in a 70 ° C oven and ground with a mortar to obtain a porous foam carbon material.
[0063] Example 4
[0064] 10 g of copper-nickel alloy powder was added to a high-temperature reactor, and then 5 mL of ethanol was added and stirred evenly, and then 20 g of dry ice was added, and the temperature was increased to 600 ° C at a heating rate of 5 ° C / min, and kept warm for 5 hours. After the high-temperature reactor was completely cooled to room temperature, the reaction product was taken out, and the reaction product was soaked in 5 mol / L hydrochloric acid for pickling at 70 ° C for 12 hours, and then centrifuged at a speed of 10000 r / min to separate the solid and liquid, and the solid product after solid-liquid separation was dried in a 70 ° C oven and ground with a mortar to obtain a porous foam carbon material.
[0065] Example 5
[0066] 10 g of copper-nickel alloy powder was added to a high-temperature reactor, and then 6 mL of ethanol was added and stirred evenly, and then 20 g of dry ice was added, and the temperature was increased to 600 ° C at a heating rate of 5 ° C / min, and kept warm for 5 hours. After the high-temperature reactor was completely cooled to room temperature, the reaction product was taken out, and the reaction product was soaked in 5 mol / L hydrochloric acid for pickling at 70 ° C for 12 hours, and then centrifuged at a speed of 10000 r / min to separate the solid and liquid, and the solid product after solid-liquid separation was dried in a 70 ° C oven and ground with a mortar to obtain a porous foam carbon material.
[0067] Example 6
[0068] 10 g of copper-nickel alloy powder was added to a high-temperature reactor, and then 8 mL of ethanol was added and stirred evenly, and then 20 g of dry ice was added, and the temperature was increased to 600 ° C at a heating rate of 5 ° C / min, and kept warm for 5 hours. After the high-temperature reactor was completely cooled to room temperature, the reaction product was taken out, and the reaction product was soaked in 5 mol / L hydrochloric acid for pickling at 70 ° C for 12 hours, and then centrifuged at a speed of 10000 r / min to separate the solid and liquid, and the solid product after solid-liquid separation was dried in a 70 ° C oven and ground with a mortar to obtain a porous foam carbon material.
[0069] Example 7
[0070] 10 g of copper-nickel alloy powder was added to a high-temperature reactor, and then 7 mL of ethanol was added and stirred evenly, and then 15 g of dry ice was added, and the temperature was increased to 600 ° C at a heating rate of 5 ° C / min, and kept warm for 5 hours. After the high-temperature reactor was completely cooled to room temperature, the reaction product was taken out, and the reaction product was soaked in 5 mol / L hydrochloric acid for pickling at 70 ° C for 12 hours, and then centrifuged at a speed of 10000 r / min to separate the solid and liquid, and the solid product after solid-liquid separation was dried in a 70 ° C oven and ground with a mortar to obtain a porous foam carbon material.
[0071] Example 8
[0072] 10 g of copper-nickel alloy powder was added to a high-temperature reactor, and then 7 mL of ethanol was added and stirred evenly, and then 18 g of dry ice was added, and the temperature was increased to 600 ° C at a heating rate of 5 ° C / min, and kept warm for 5 hours. After the high-temperature reactor was completely cooled to room temperature, the reaction product was taken out, and the reaction product was soaked in 5 mol / L hydrochloric acid for pickling at 70 ° C for 12 hours, and then centrifuged at a speed of 10000 r / min to separate the solid and liquid, and the solid product after solid-liquid separation was dried in a 70 ° C oven and ground with a mortar to obtain a porous foam carbon material.
[0073] Example 9
[0074] 10 g of copper-nickel alloy powder was added to a high-temperature reactor, and then 7 mL of ethanol was added and stirred evenly, and then 25 g of dry ice was added, and the temperature was increased to 600 ° C at a heating rate of 5 ° C / min, and kept warm for 5 hours. After the high-temperature reactor was completely cooled to room temperature, the reaction product was taken out, and the reaction product was soaked in 5 mol / L hydrochloric acid for pickling at 70 ° C for 12 hours, and then centrifuged at a speed of 10000 r / min to separate the solid and liquid, and the solid product after solid-liquid separation was dried in a 70 ° C oven and ground with a mortar to obtain a porous foam carbon material.
[0075] Example 10
[0076] 10 g of iron-nickel alloy powder was added to a high-temperature reactor, and then 7 mL of toluene was added and stirred evenly, and then 20 g of dry ice was added, and the temperature was increased to 700 ° C at a heating rate of 5 ° C / min, and kept warm for 4 hours. After the high-temperature reactor was completely cooled to room temperature, the reaction product was taken out, and the reaction product was soaked in 5 mol / L hydrochloric acid for pickling at 80 ° C for 15 hours, and then centrifuged at a speed of 10000 r / min to separate the solid and liquid, and the solid product after solid-liquid separation was dried in a 75 ° C oven and ground with a mortar to obtain a porous foam carbon material.
[0077] Comparative Example 1
[0078] The difference between Comparative Example 1 and Example 2 is that no copper-nickel alloy powder is added.
[0079] Comparative Example 2
[0080] The difference between Comparative Example 2 and Example 2 is that an equal amount of copper powder is added instead of copper-nickel alloy powder.
[0081] Comparative Example 3
[0082] The difference between Comparative Example 3 and Example 2 is that an equal amount of nickel powder is added instead of the copper-nickel alloy powder.
[0083] Comparative Example 4
[0084] The difference between Comparative Example 4 and Example 2 is that an equal amount of starch is added instead of ethanol.
[0085] Comparative Example 5
[0086] The difference between Comparative Example 5 and Example 2 is that an equal amount of water is added instead of dry ice.
[0087] The carbon materials prepared in all embodiments and all comparative examples were tested, and the results are shown in Table 1. The strength is represented by the initial stress retention rate after 80 cycles of testing at 50% strain, and the structural stability is represented by whether the structure collapses after calcination at 800°C in air for half an hour.
[0088] Table 1
[0089]
[0090] It can be seen from Table 1 that the carbon materials obtained in all embodiments are porous foam carbon materials with special morphology and structure, and have high strength and excellent structural stability. Comparative Examples 1 to 3 show that the reaction temperature has a certain influence on porosity, specific surface area and density. Under the same copper-nickel alloy powder, ethanol and dry ice mass conditions, the porous foam carbon material structure obtained at a reaction temperature of 600°C has a larger specific surface area, a smaller density, a higher porosity, and higher stability and strength; Comparative Examples 2, 4 to 6 show that the structure of the porous foam carbon material obtained is related to the proportion of the carbon source, and as the carbon source increases, the structural performance first increases and then decreases; Comparative Examples 2, 7 to 9 show that the structure of the porous foam carbon material obtained is related to the mass of dry ice, and when the mass of dry ice is 20g, the porous foam carbon material structure obtained is optimal.
[0091] In Comparative Example 1, since copper-nickel alloy powder is not added, there is no catalyst, resulting in low graphitization degree, specific surface area, porosity and structural stability of the carbon material; Comparative Examples 2 and 3 use a single metal as a catalyst, and the single catalyst cannot form a material with a high specific surface area, and the stability is poor; Comparative Example 4 uses a solid carbon source, and the solid carbon source causes the reaction to be uneven, and the porosity and stability of the obtained material are low; Comparative Example 5 uses water as the supercritical medium, and the use of a liquid medium makes it difficult for the material structure to change, and the performance of the material obtained under this environment is average.
[0092] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0093] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a porous foam carbon material, characterized in that: The steps include: The alloy powder, liquid carbon source and dry ice are mixed and reacted in a supercritical carbon dioxide medium environment formed under sealed heating conditions to obtain a porous foam carbon material.
2. The method for preparing the porous foamed carbon material according to claim 1, characterized in that: The mass ratio of the alloy powder to the liquid carbon source is 10:4-10:
6.
3. The method for preparing the porous foamed carbon material according to claim 1, characterized in that: The mass ratio of the liquid carbon source to the dry ice is 4:20-6:
20.
4. The method for preparing the porous foamed carbon material according to claim 1, characterized in that: The alloy powder is selected from at least one of copper-nickel alloy powder and iron-nickel alloy powder.
5. The method for preparing the porous foamed carbon material according to claim 1, characterized in that: The liquid carbon source is selected from at least one of ethanol and toluene.
6. The method for preparing the porous foamed carbon material according to claim 1, characterized in that: Before sealing and heating, the alloy powder and the liquid carbon source are first mixed at room temperature and pressure, and then dry ice is added for sealing and heating.
7. The method for preparing the porous foamed carbon material according to claim 1, characterized in that: The reaction temperature is 500°C-700°C, the heating rate is 3°C / min-7°C / min, and the reaction time is 4h-6h.
8. The method for preparing the porous foamed carbon material according to claim 1, characterized in that: After the reaction is completed, a wet treatment is further included, wherein the temperature of the wet treatment is 70° C.-80° C. and the time is 12 h-18 h.
9. The method for preparing the porous foamed carbon material according to claim 8, characterized in that: The mixture after the wet treatment is subjected to solid-liquid separation, and the separated solid is dried at 70° C.-80° C. for 12 h-18 h.
10. A porous foamed carbon material obtained by the method for preparing a porous foamed carbon material according to any one of claims 1 to 9.